2018
DOI: 10.4103/0973-1482.171361
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of miR-371-373 cluster, a human embryonic stem cell specific microRNA cluster, in esophageal squamous cell carcinoma

Abstract: Our findings support the hypothesis that these miRNAs might play a role in tumorigenesis in esophageal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Expression of miR-371–37 cluster has been assessed in Iranian ESCC samples and demonstrated the miR-371–373 over expression in tumors compared with normal margins. It was suggested that the miR-371–373 over expression can be involved in tumorigenesis through cell cycle regulators such as CDK2, CDK4, and CDK6 [30]. MiR-451 is another important regulator of cell proliferation, migration, and apoptosis which is related to different factors such as CAB39 [103], RAB14 [96], and MIF [104].…”
Section: Main Textmentioning
confidence: 99%
“…Expression of miR-371–37 cluster has been assessed in Iranian ESCC samples and demonstrated the miR-371–373 over expression in tumors compared with normal margins. It was suggested that the miR-371–373 over expression can be involved in tumorigenesis through cell cycle regulators such as CDK2, CDK4, and CDK6 [30]. MiR-451 is another important regulator of cell proliferation, migration, and apoptosis which is related to different factors such as CAB39 [103], RAB14 [96], and MIF [104].…”
Section: Main Textmentioning
confidence: 99%
“…Among them, the miR-371–373 cluster and the miR-302 cluster are found overexpressed in TGCTs. Members of the miR-371–373 cluster are the prevalent miRNAs in human embryonic stem cells and are involved in self-renewal processes and in maintaining the pluripotency status of ESCs [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, human embryonic stem cells (ESCs) contain microRNA-371–373 (miR-371–373) gene clusters in a highly abundant form, indicating that miR-371–373 genes are important in the maintenance of stemness in ESCs [ 13 ]. Through this, the miR-371–373 gene cluster, involved in signaling pathways, such as the Wnt/β-catenin pathway, can promote stem cell self-renewal and oncogenesis in various tissues [ 14 ].…”
Section: Introductionmentioning
confidence: 99%